New directions using reporter enzyme fluorescence (REF) as a tuberculosis diagnostic platform. (December 2016) - Sule, Preeti; Tilvawala, Ronak; Behinaein, Parnia; Walkup, Grant K.; Cirillo, Jeffrey D.
Summary: Although tuberculosis (TB) is one of the most common causes of morbidity and mortality in humans worldwide and diagnostic methods have been in place for more than 100 years, diagnosis remains a challenge. The main problems with diagnosis relate to the time needed to obtain a definitive result, difficulty in obtaining sputum, the primary clinical material used, and the ability of the causative agent, Mycobacterium tuberculosis, to cause disease in nearly any tissue within the body. In order to decrease incidence of TB, discovery of a novel interventions will be required, since current technologies have only been able to control numbers of infections, not reduce them. Diagnostic innovation is particularly needed because there are no effective pediatric or extrapulmonary TB diagnostic methods and multiple-drug resistance is only identified in less than 25% of those patients that are thought to have it. The most common diagnostic method worldwide remains acid-fast stain on sputum, with a threshold of ∼10, 000 bacteria/ml that is only reached ∼5–6 months after development of symptoms. In order to obtain definitive diagnostic results earlier during the disease process, we have developed a diagnostic method designated reporter enzyme fluorescence (REF) that utilizes BlaC produced by M. tuberculosis and custom substrates to produce a specific fluorescent signal with as few as 10 bacteria/ml in clinical samples. We believe that the unique biology of the REF technique will allow it to contribute new diagnostic information that is complementary to all existing diagnostic tests as well as those currently known to be in development.